(untitled) (Advances in Applied Mathematics and Mechanics, 2013)
Matching boundary conditions (MBC's) are proposed to treat scalar waves in the body-centered-cubic lattices. By matching the dispersion relation, we construct MBC's for normal incidence and incidence with an angle alpha. Multiplication of MBC operators then leads to multi-directional absorbing boundary conditions. The effectiveness is illustrated by the reflection coefficient analysis and wave packet tests. In particular, the designed M1M1 treats the scalar waves in a satisfactory manner.